Management Orthopedic Patient With Covid 19, A Picture Of Patient Safety - Luh Tantri, Ni; Fauzi, Mahmud; Rohman, Rohman; Rochma, Erwi; Isnaini, Berry; Dwi, Retno (Publisher Cv. Inara, 2023)
This study will describe management policies to maintain hospital services by putting safety and analyze epidemiological data on orthopedic patient with covid-19 infection who were admitted during covid-19 pandemic. A retrospective descriptive study of orthopedic patients with covid-19 infection profile during 1st wave of covid-19 Pandemic (January - March 2021). Modification of patient and staff work flow were also made, based on risk of transmissions, this include rescheduling elective surgery and promoting telemedicine. For patient who were admitted for urgent surgery, transition room were made for screening covid-19 infection before operation, there also a negative pressure operation room for patient who need an emergency operation. There were 38 orthopedic patients admitted to transition room, 18 patient (47.36%) were confirmed covid-19 infection. There are slight fewer female patient with confirmed Covid-19, compare to the male patient 8 (44.4%) vs 10 (55.6%) patient. The Patient’s age ranged from 5 to 79 years old, with average of 46.27 years old (SD 20.63). With most patient were 56-65 years old. The patients’ diagnosis and demographics data were described in table 1. Five patients (27.8 %) with mild covid-19, nine patients (50 %) with moderate covid-19 and four patients (22.2 %) with severe covid-19. Among 18 patients with confirmed covid-19, seven patients (38.9%) had hypertension and three patients(16.7%) had diabetes . The Laboratory data shows 13 patients (72.7%) had abnormal NLR with all patients had increased D Dimer. Average length of stay were 12.78 days, Range 2 days to 21 days; SD 5,53) with eleven patients (61.1%) underwent operation procedure and 7 (38.9%) patients were on conservative treatment. There was 1 (1.8%0 death case recorded, among patients with confirmed COVID-19, this was a C3 Spinal Cord Injury patient with tetraplegia and respiratory failure. During this period there were 16 (2.5% from 636 staff) were diagnosed with covid-19, among them 60% in red area ( operation room, Emergency unit, polyclinics, isolation room and laboratory). There were no documented in hospital death among orthopedic patient with confirmed covid-19 who underwent surgery procedure. Covid-19 had disrupted many aspects in hospital services. Our Hospital had develop new policies and strategies to minimize covid-19 transmission during the 1st wave covid-19 pandemic. Preoperative screening, proper personal protective equipment’s, and strict transmissions control successfully minimize covid-19 transmission in our hospital. Orthopedics patient with Covid-19 infection, that require urgent surgery were admitted to isolation room. Prompt treatment according to WHO Guideline were given.